PENGARUH INTELLECTUAL CAPITAL DAN INTELLECTUAL CAPITAL DISCLOSURE KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2013-2015) - Aprilia Prastiwi, 13.05.52.0248; Susilowati, Yeye (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of intellectual capital and intellectual capital disclosure influence to the financial performance. In this study popuation are used companies registered inManufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013-2015.The sampling technique using purposive sampling. Mechanical testing data is to use a multipe linear regression analysis. The analysis showed that the variables Physical Capital (VACA) positif significant effect on influence to the financial performance. Human Capital (VAHU) positif significant effect on influence to the financial performance. Structural Capital Value Added (STVA) and (ICD) do not have any influence to the financial performance.Keywords: Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA),Intellectual Capital Disclosure (ICD), Return on Assets (ROA)